Supporting clinician educators to achieve “work-work balance” - Maniate, Jerry M; Dath, Deepak; Cooke, Lara; Leslie, Karen; Snell, Linda; Busari, Jamiu O (Canadian Medical Education Journal, 2016)
Clinician Educators (CE) have numerous responsibilities in different professional domains, including clinical, education, research, and administration. Many CEs face tensions trying to manage these often competing professional responsibilities and achieve “work-work balance.” Rich discussions of techniques for work-work balance amongst CEs at a medical education conference inspired the authors to gather, analyze, and summarize these techniques to share with others. In this paper we present the CE’s “Four Ps”; these are practice points that support both the aspiring and established CE to help improve their performance and productivity as CEs, and allow them to approach work-work balance.